The Role of OCT Angiography in the Assessment of Epiretinal Macular Membrane - Daniela Bacherini; Francesco Dragotto; Tomaso Caporossi; Chiara Lenzetti; Lucia Finocchio; Alfonso Savastano; Maria Cristina Savastano; Francesco Barca; Martina Dragotto; Lorenzo Vannozzi; Francesco Nasini; Francesco Faraldi; et al. (Journal of Ophthalmology)
Background. The aim of this observational study is to assess pre- and postoperative retinochoroidal vascular changes in patients undergoing epiretinal macular membrane (ERM) surgery by using optical coherence tomography angiography (OCTA). Materials and Methods. 23 eyes affected by ERM and those which underwent phacovitrectomy associated with ERM peeling were enrolled. They were evaluated using structural OCT and OCTA before surgery and at 1, 3, and 6 months postoperatively. Results. We found a statistically significant (p < 0.05) increase in the superficial capillary plexus vessel density (VD) from baseline to the 6-month follow-up. We observed a large increase in both the perfusion density (PD) and the VD of the deep capillary plexus between baseline and the 6-month follow-up (p < 0.001). A significant decrease in the VD and PD of the choriocapillaris (CC) from baseline to the 1st month and a significant increase in CC perfusion density at the 6-month follow-up compared to the preoperative value were revealed. The FAZ area and perimeter after surgery significantly increased during the follow-up (p < 0.001) at baseline retinal and choroidal plexi with a lower PD or VD correlated with worse visual acuity (p < 0.05 for all plexi). At baseline and at the 1-month follow-up, a significant correlation was found with the FAZ area and the FAZ perimeter: a smaller FAZ area or a smaller FAZ perimeter was correlated to a lower visual acuity. Before surgery, negative correlations (p < 0.05) were found between the Govetto ERM stages and perfusion density of the SCP and the DCP and between the Govetto stages and vessel density of the DCP. Conclusions. In our study, OCTA detected vascular alterations induced by the presence of the ERM, allowing several correlations with functional data. In these patients, OCTA may be useful to add new potential surgical prognostic factors.